THE NEED FOR ORAL REHABILITATION IN OPEN BITE - Viorica Țărmure; Radu Septimiu Câmpian; Ecaterina Ionescu; Mariana Păcurar; Paula Jiman; Andreea Pop (Romanian Society of Oral Rehabilitation, 2018)
Aim of the study .The open bite is a part of dentomaxillary anomalies and is classified by anatomic open bite and functional open bite. In this study, we demonstrated the frequency of the open bite , the dysfunctional factors involved as well as the etiopathogenesis of the anomaly. Materials and methods. We did a retrospective study for a group of 290 patients who were treated at the clinic Orthodontics "Iuliu Haţieganu" Cluj Napoca (2015-2017). The study was based on data collected from completed forms for each patient. Results. The data were systematized in tables and were subjected to statistical analysis. Our study focuses on a group of 290 patients of which 26 (9%) have an open bite, and 264 patients (91%) have other dentomaxillary anomalies. Conclusions . Prophylaxis means and interception will eliminate dysfunctional factors and ensure the normal development of the dentomaxillary apparatus.